2013
DOI: 10.3390/ijms140815724
|View full text |Cite
|
Sign up to set email alerts
|

Mild Oxidative Damage in the Diabetic Rat Heart Is Attenuated by Glyoxalase-1 Overexpression

Abstract: Diabetes significantly increases the risk of heart failure. The increase in advanced glycation endproducts (AGEs) and oxidative stress have been associated with diabetic cardiomyopathy. We recently demonstrated that there is a direct link between AGEs and oxidative stress. Therefore, the aim of the current study was to investigate if a reduction of AGEs by overexpression of the glycation precursor detoxifying enzyme glyoxalase-I (GLO-I) can prevent diabetes-induced oxidative damage, inflammation and fibrosis i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
21
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 41 publications
5
21
0
Order By: Relevance
“…We consistently found that CEL in particular was strongly associated with incident cardiovascular events. This finding is in line with the concept that methylglyoxal and its derived AGEs, such as CEL, play the most important role in AGE accumulation (1) and development of diabetes complications (34,35). However, this finding should be interpreted with some caution, as for CML and pentosidine, we are likely to underestimate associations with outcome due to residual negative confounding from obesity, as BMI (or waist circumference) does not completely capture adiposity.…”
Section: Discussionsupporting
confidence: 85%
“…We consistently found that CEL in particular was strongly associated with incident cardiovascular events. This finding is in line with the concept that methylglyoxal and its derived AGEs, such as CEL, play the most important role in AGE accumulation (1) and development of diabetes complications (34,35). However, this finding should be interpreted with some caution, as for CML and pentosidine, we are likely to underestimate associations with outcome due to residual negative confounding from obesity, as BMI (or waist circumference) does not completely capture adiposity.…”
Section: Discussionsupporting
confidence: 85%
“…In a rat model of type 1 diabetes, it has been shown that MGO reduces the ability of SERCA2a to perform this translocation, resulting in diastolic dysfunction of the heart [170]. It is interesting that the overexpression of GLO1 does attenuate mild oxidative damage in the diabetic rat heart, by reducing MGO levels [171].…”
Section: Macrovascular Complications In Diabetesmentioning
confidence: 99%
“…Alternatively, MG can form from lipid peroxidation mechanisms, known to be exacerbated with oxidative stress, a common characteristic of insulin resistance and T2DM ( 13 ). MG induces pathways known to contribute to insulin resistance including: (1) oxidative stress caused by damage to mitochondria ( 31 ) and mitochondrial DNA ( 32 ), (2) generation of AGEs [for more information on the independent effects of AGEs in diabetes and diabetic complications, the reader is directed to a recent review by Brings et al ( 33 )] and (3) inflammation mediated through the Receptor for Advanced Glycation Endproducts (RAGE) signaling ( 34 36 ). RAGE is highly expressed in skeletal muscle ( 37 , 38 ) and upon binding of a RAGE-ligands (i.e., MG-H1) a well characterized inflammatory signaling cascade ensues ( 39 41 ).…”
Section: Mg and Dicarbonyl Stress In Skeletal Muscle And Insulin Resimentioning
confidence: 99%